The enhancement of the cellulolytic activity of cellobiohydrolase I and endoglucanase by the addition of cellulose binding domains derived from trichoderma reesei - Lemos, M. A. (2003)
The effect of isolated cellulose binding domains (CBDs) on the hydrolysis of filter paper and microcrystalline cellulose by both cellobiohydrolase I and endoglucanase, was studied. CBDs were obtained by proteolysis from cellulases using a scaled-up variant of our previous method. Experiments were performed for different enzyme/substrate ratios in both the absence and presence of CBDs. Hydrolysis of filter paper by intact cellobiohydrolase I in the presence of additional CBDs was found to have a synergistic effect, leading to an increase of the sugar production of up to 30%. The effect was less pronounced using microcrystalline cellulose, where an increase up to 16% was observed. Similar trends were found during the hydrolysis of both substrates by endoglucanase.